THE IMPACT OF FINANCIAL PLANNING ON ACHIEVING SUSTAINABLE DEVELOPMENT (FRANCE AS A MODEL ( (World Economics and Finance Bulletin, 2026)
This research is a model that simulates the principle of harnessing financial planning to serve the aims of sustainable development in accordance with its pillars, and focuses on rethinking the methods of setting allocations and budgets, as well as production and consumption, with the aim of reducing the waste of natural resources that constitute a major obstacle to the requirements of sustainable development. Adopting this model has become an inevitable necessity for most countries to ensure the success of their economic and social activities. Among the leading countries in this field, we find France. In order to explain and analyze its role in linking the two main research variables (financial planning and sustainable development), this research was prepared in three sections, and we reached a number of results and proposals that focus on the fact that France has intensified its financial, political and social efforts to achieve the aims of sustainable development, the most important of which are reducing environmental damage and the great waste of energy and preserving the rights of future generations